P73 The Rate Of Incidental Synchronous Pathology On Pet-ct Scans Performed For Thoracic Malignancy And Subsequent Impact On Lung Cancer Pathways. (10th November 2014) - Jones, TRE; Curtis, HJ
Abstract : Introduction: NICE (CG121) recommends that all patients potentially suitable for curative intent treatments are offered PET-CT, and that they are treated within 62 days of their urgent referral and within 31 days of the decision to treat. There are case reports and three large studies regarding incidental findings on PET-CT performed for thoracic malignancy. These studies were based in Sheffield, Australia and Switzerland, with a rate of significant incidental findings of 21%, 12% and 9% respectively. There are no studies regarding the impact on referral pathways. We aimed to identify the rate of incidental synchronous pathology on PET-CT for thoracic malignancy in our local population of 190, 000 and the impact of these on referral pathways. We serve a local authority district ranked 43/326 in the English Index Multiple Deprivation in 2010 (rank of 1 being most deprived). Methods: Identifying patients from our thoracic MDT database, we retrospectively analysed electronic patient records for those with synchronous pathology on PET-CT between November 2012 and October 2013. Data collected included primary diagnosis, synchronous pathology, referral timelines and reasons for delays. Results: 108 patients had a PET-CT for investigation of thoracic malignancy. 29 incidental findings were found in 28 patients (28/108;26%); see chart-1. 20 patients (20/108;19%) required further investigation/referral for their synchronous pathology. 22 of these 28 patients were ultimately diagnosed and treated for thoracic malignancy. Referral to treatment was delayed in 8 patients (8/108;7%), but only in 1 (1/108;1%) as a direct result of management for their synchronous pathology. Conclusions: A high number of patients undergoing PET-CT have synchronous pathology. Compared with previous UK data we found a higher rate of synchronous pathology. This may reflect a higher burden of disease in the North East of England. Synchronous findings have a limited impact on referral to treatment pathways. However they can result in more investigations and trips to hospital, which may have a psychological impact on patients already going through a stressful life event. Perhaps this should be highlighted at time of decision to perform PET-CT.